Strength and agility with Brynn: a senior fitness research project - McClure, Brynn, author (Colorado State University. Libraries, 2024)
Senior fitness is a vital component to examine within a community to assess the physical health of the older generations. Awareness of physical health is increasingly important as we age; furthermore, fitness levels will typically decline with age. To test senior citizens' physical fitness, a fitness-test-based group class was implemented at The Worthington Independent Living Center. A total of 10 weeks of fitness classes were implemented in which fitness-test data was collected. During the first three weeks class was held once a week, then during the last seven weeks class was held twice a week. The first three weeks of class consisted of solely subjective survey data. The objective survey for new participants asked medical health history questions and current fitness levels of each participant. For the next 10 weeks an existing participant survey was given once every two weeks. For this survey the seniors self-analyzed their improvement in six specific physical health factors since coming to class, balance, upper body strength, lower body strength, ability to stand from a chair, flexibility and ease of walking up stairs. During the last seven weeks of class objective data was collected. This included the numerical values from each participant's performance on the national fitness tests. Each class consisted of the same six fitness-battery tests geared towards seniors and acts of daily living (ADLs). These tests assessed lower and upper body strength, lower and upper body flexibility, endurance, and agility. In respective order the class was set up with a chair sit to stand test, an 8-foot agility get up and go test, chair sit and reach, 2-minute step test, bicep curl test, and finally a back scratch test. After data collection, the average values from the fitness tests of participants at The Worthington Independent Living Center were compared to the national normative values for seniors. Participant's average values were separated by age and sex. We found that both age groups and sexes of seniors at The Worthington were above the national average for upper and lower body strength, and endurance. The 85-94 age group in both sexes was below average for the lower body flexibility test. All groups were below average for the upper body flexibility test besides women ages 85-94, and all groups for the agility test were below average. Regular participants saw improvements in four out of the six fitness tests over 10 weeks. This project met its goals of increasing fitness levels in senior participants, evaluating how they measure up in comparison with the national normative values, and what areas they can improve in, which would consequently be flexibility and agility.
Keywords: senior fitness; strength; agility; endurance; fitness test; normative values; flexibility